Kinerja Pegawai dalam Pelayanan Logistik Pasca Bencana Pada Kantor BPPD Kabupaten Halmahera Selatan - La Suhu, Bakri; Ibrahim, Abdulhalil Hi; Jafar, Abdilah; Wance, Marno (Journal of Government Science Studies, 2023)
This study uses a qualitative research type by focusing on the study of the performance of South Halmahera Regency BPBD employees in post-disaster logistics services. Qualitative research emphasizes inductive analysis, not deductive analysis. The data sources used are primary data and secondary data, with data collection techniques through observation, interviews and documentation. Based on the results of the study, it was shown that the performance of BPBD employees in South Halmahera Regency, seen from the productivity aspect of post-disaster logistics services, had not been maximally implemented. The aspect of the quality of logistics services has also not been maximally implemented, because the timeliness of logistics services is sometimes not timely when distributing them to villages, while the attitude of BPBD staff is very good. The aspect of employee responsiveness has been very good in post-disaster logistics services, employees are very responsive to various logistical issues and are not selective in providing logistics services.